Intersection of race, gender, and nationality in teaching about race and racism. Issue 1 (2nd January 2018) - Constance-Huggins, Monique
Abstract: Teaching about race and racism is important in social work education, yet at times it can present perplexing experiences for some faculty members. Using the concept of intersectionality, this paper presents a narrative on my experience of teaching race and racism as a Black, female professor from the Caribbean. Examples of my pedagogical responses during these experiences are presented.